b+c^2 There is no way to simplify that.
The like terms are sums of b terms and c terms separately 5c+2c+3c+4b 5c +2c + 4b + 3c => 10c + 4b
It is: 4b+6
It is an expression that can be simplified to: 1-4b-5c
It is 2a-b simplified
b times b times b = b3 b plus b plus b = 3b
It is: b+4 when simplified
There is an ambiguity whether you square the sum of a plus b, or only b. In any case, I don't think you can simplify this expression.
2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1
Your equation cannot be solved. So we simplify using fun algebra! 4b + b = 5b
According to the Law of Absorption, A+(A*B) = A. Boolean B is "absorbed" by A.Similarly, A*(A+B) = A.
b × b = b²
Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?
sqrt(a2 + b2) can't be simplified. Neither can (a2 + b2) .
20a plus 14 will be 34a minus 8a minus 7 34a minus 8 is 26a minus 7 is 19a. The single b is 1b plus 6b which is 7b minus 2b equals 5b.
4a2 + 4ab - y2 + b2 You cannot simplify this expression because it does not contain like terms, but you can factor it such as: 4a2 + 4ab - y2 + b2 = (4a2 + 4ab + b2) - y2 = (2a + b)2 - y2 = [(2a + b) - y][(2a + b) + y]
Simplify this: A = 36.513, A+B = 40.968, What is B? Well it's 40.968 - 36.513 = 4.455